Environmental Investment Decision of Green Supply Chain considering the Green Uncertainty - Shaobo Wu; Xun Yao; Guangdong Wu (Complexity)
The uncertainty of eco-friendly intermediate components has an important impact on green supply chain decisions. In this paper, the Stackelberg game model of green investment decision-making among enterprises is established by considering the case of the supplier’s green investment alone and the case of the manufacturer and the supplier’s joint green investment. The influence of green uncertainty on enterprise’s decision-making is analyzed, and the green investment decision-making strategies of both sides in two cases are compared. There are four main conclusions derived from the results: (i) with the increase in the supplier’s green cost coefficient, the supplier will reduce the green investment and the manufacturer will reduce the share of the green costs; (ii) with a decrease in uncertainty for eco-friendly intermediate components and the increase in their feasibility factor, the supplier will increase the greenness of intermediate components and increase the investment in environment, and the manufacturer will reduce the share of the green costs; (iii) the increase in the manufacturer’s share of green costs will promote the supplier to increase the greenness of intermediate components and increase its green investment, which shall increase the supplier’s optional choice space of for green investment; (iv) in the case of the manufacturer and the supplier jointly making a green investment, the threshold value for the environmental input of the supply chain members (i.e., the manufacturer and the supplier) is lower, and the supply chain members will have more choice space. At the same time, the care for environment in the case of a cooperative is higher than that in the case of a supplier investing alone.